Evaluation of the modified computed tomography severity index (MCTSI) and computed tomography severity index (CTSI) in predicting severity and clinical outcomes in acute pancreatitis. Issue 1 (22nd December 2020) - Alberti, Piero; Pando, Elizabeth; Mata, Rodrigo; Vidal, Laura; Roson, Nuria; Mast, Richard; Armario, David; Merino, Xavier; Dopazo, Cristina; Blanco, Laia; Caralt, Mireia; Gomez, Concepción; et al.
Abstract : Objective: Our main purpose was to compare the modified computed tomography severity index (MCTSI), computed tomography severity index (CTSI), and acute physiological and chronic health evaluation (APACHE)‐II predictions regarding severity according to the revised Atlanta classification 2012 and local complications in acute pancreatitis in a consecutive prospective cohort. Methods: One hundred and forty‐nine patients diagnosed with acute pancreatitis were prospectively enrolled. APACHE‐II, MCTSI, and CTSI were calculated for all cases. Severity parameters included persistent organ or multiorgan failure, length of hospitalization, the need for intensive care, death, and local complications (intervention against necrosis and infected necrosis). Area under the receiver operating characteristic curve (AUROC) was calculated and the value of scoring systems was compared. Results: Both CTSI and MCTSI were associated significantly with all the evaluated severity parameters and showed a correlation between imaging severity and the worst clinical outcomes. Persistent organ failure, persistent multiorgan failure, and death were found in 30 (20.1%), 20 (13.4%), and 13 (8.7%) patients, respectively. The most common extrapancreatic finding was pleural effusion in 76 (51.0%) patients. The AUROC for CTSI was higher for predicting persistent organ failure (0.749, 95% confidence interval [CI] 0.640‐0.857), death (AUROC 0.793, 95% CI 0.650‐0.936), intervention against necrosis (AUROC 0.862, 95% CI 0.779‐0.945), and infected necrosis (AUROC 0.883, 95% CI 0.882‐0.930). Conclusions: CT indexes outperformed the classic APACHE‐II score for evaluating severity parameters in acute pancreatitis, with a slight advantage of CTSI over MCTSI. CTSI accurately predicted pancreatic infections and the need for intervention. Abstract :